การลดซีโอดีและสีในน้ำชะขยะจากหลุมฝังกลบของเสียอันตรายโดยใช้ เฟอริกคลอไรด์ ซีโอไลต์ และไฮโดรเจนเปอร์ออกไซด์ - วรันธร คำพิลา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The objective of this study is to remove COD and colour of leachate from secure landfill which is high COD about 43,478 mg/l and black brown colour, by using ferric chloride, zeolite and hydrogen peroxide. The results found that coagulation process the concentration of ferric chloride 700 mg/l at pH 4 can reduce 55.79% of COD and 51.32% of colour. Using the treated leachate by ferric chloride, at pH 4 to remove COD and colour by zeolite. The adsorption efficiency by 9 g of zeolite at pH 4 and contact time 90 min can reduce 17.96% of COD and reduce 85.70% of colour. Using the treated leachate by ferric chloride and optimum dose of zeolite to remove COD and colour by H2O2 found that the concentration of H2O2 150 mg/l at pH 4 can reduce COD and colour 4.92%, 94.68% respectively. Using the treated leachate by ferric chloride and optimum dose of zeolite at pH 4 the concentration of H2O2 150 mg/l at and oxidized by Fe2+ found that the optimum dose of Fe2+ 0.03 g can reduce 1.28%, -32.72% of COD and colour respectively. Totally these processes include that coagulation by ferric chloride, adsorption by zeolite and oxidation by hydrogen peroxide can remove 65.52% of COD and 99.64% of colour. The total chemical cost of treatment is 1,260 Baht per one cubic meter of leachate.